Innovations in Risk Management as Exemplified by the Polish Insurance Market - ÅšliwiÅ„ski, Adam; Michalski, Tomasz; KarmaÅ„ska, Anna (Journal of Reviews on Global Economics, 2013)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The era of knowledge based economy, which the world is dynamically entering, reveals many new factors and necessities which a modern company needs to consider and cope with if it wishes to stay on in business. The innovativeness of business activity, in a broad meaning of the word, is an area of significant factors. Holistically, one may ask about the borders of innovation applied in business. Are they determined by: the actual needs of end consumers and as a consequence the needs of companies participating in the chain of value delivered to these customers or primarily the actual needs to earn on corporate investments on the customer value chain? <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: ’Arial’,’sans-serif’; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: EN-US;" lang="EN-GB">This paper analyses the problem of management of innovation programmes and projects introduced by companies from the microeconomic perspective. Its main aim is to show a new approach to innovation cost management and the innovation activity of the insurance sector in Poland. The paper consists of two sections. The first one describes innovation cost management. Innovative companies should be supported by the insurance sector. They should also apply knowledge and appropriately analyse and allocate costs within the algorithms of behaviour compliant with the risk management. The second section analyses the Polish insurance sector with the Multivariate Statistical Analysis. The paper ends with the conclusions with regard to the insurance sector. The examination of the sector shows that the insurance market in Poland in the analysed period was not innovative and it did not create innovation supporting services (and it is where the insurance risk appears due to the financial aspects of innovation).<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE TH <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>